Peningkatan Kompetensi Lulusan SMK Taruna Karya 1 Karawang dalam Bidang Jaringan Transmisi Fiber Optik guna Memenuhi Standar Kompetensi sesuai SKKNI - Lela Nurpulaela; Arnisa Stefanie; Ridwan Satrio Hadikusuma; Dedi Pahroji (Peneliti.net, 2022)
The Covid-19 pandemic, which has been around for more than a year, has limited aspects of life, one of which is education. The learning process that should be carried out face-to-face, then switches to online or face-to-face. The PKM (Community Service) activity